Hot Springs Mercury Deposition At McDermitt Mine Humboldt County, Nevada ? Introduction - Michael W. Roper (Society for Mining, Metallurgy & Exploration, 1976)
McDermitt Mine is located in northern Humboldt County, Nevada, approximately 5 miles south of the Orgeon-Nevada line (Figure I), within the Opalite Mining District. The operation is a joint venture between Placer Amex Inc., San Francisco, and Mineral Exploration Company Ltd., a limited partnership. The McDermitt orebody possesses a discontinuous, gently dipping blanket-like form within 150 feet of the surface over an area 2200 by 2500 feet. The ore zone averages 20 feet in thickness. The ore minerals consist of cinnabar (HgS) and corderoite (Hg3S2C12) deposited parallel to bedding within argillized, Miocene age, tuffaceous lacustrine sediments. Exploration indicates reserves of approximately 3,000,000 tons ore at a grade of 10 pounds mercury per ton (0.5%) An open pit mining operation utilizing scrapers and bulldozers supplies a concentrator with 700 tons of ore per day. The milling operation consists of autogenous grinding, flotation concentration, concentrate dewatering, and tailing disposal, with a design capacity of 100 tons per hour. The furnace section consists of a concentrate filter, vertical six hearth furnace, mercury condensing system, and exhaust gas scrubbing systems. It has a design capacity of 1000 pounds of dry concentrate per hour. The McDermitt orebody is situated about 2000 feet north of the Cordero Mine which, with adjacent properties, produced over 115,000 flasks (76 pounds per flask) mercury from 1941 to 1972' Two other major mercury producers in the district have been the Bretz and Opalite Mines, located in southern Malheur County, Oregon, within 5 miles of the Oregon-Nevada line. Bretz and Opalite have produced about 14,800 and 12,370 flasks mercury respectively, from 1926 to 1965.1/